Health Aid and Infant Mortality - Newhouse, David Locke (International Monetary Fund, 2007)
This paper examines the relationship between health aid and infant mortality, using data from 118 countries between 1973 and 2004. Health aid has a statistically significant effect on infant mortality: doubling per capita health aid is associated with a 2 percent reduction in the infant mortality rate. For the average country, this implies that increasing per capita health aid by US$1.60 per year is associated with 1.5 fewer infant deaths per thousand births. The estimated effect is small, relative to the targets envisioned by the Millennium Development Goals